ECG Simulator Based on Microcontroller Equipped with Arrhythmia Signal - Bedjo Utomo; I Dewa Gede Hari Wisana; Torib Hamzah; Lamidi Lamidi; Denis Kurniar Wicaksono; Sedigheh Ashgari Baighout; M. Ridha Mak'ruf; Andjar Pudji (Jurnal Teknokes, 2022)
Electrocardiograph (ECG) is one of the diagnostic sciences that is often studied in modern medicine, used to detect damage to the components of the heart or disorders of the heart rhythm called arrhythmias. The purpose of this research is to develop an Electrocardiograph simulator that is equipped with arrhythmia. The main design consists of an Arduino Mega 2560 microcontroller, MCP4921 DAC (Digital to Analog Converter) circuit, a network resistor, and a sensitivity selection circuit. The MCP4921 type DAC converts the digital signal data into analog data which will then be forwarded to the resistor network circuit as a signal formation for each lead. The basic signal image data used for the formation of normal Electrocardiograph and arrhythmias were taken from the Electrocardiograph recorder using Phantom Electrocardiograph. Based on the readings on the Beat Per Minute setting of the module to the Beat Per Minute printout on the Electrocardiograph recorder, the error rate value for the Normal Sine Rhythm parameter is 0.790% for Beat Per Minute 30, 0.383% for Beat Per Minute 60, 0.535% for Beat Per Minute 120, 0.515% for Beat Per Minute 180 and 0.593% for Beat Per Minute 240. The error rate for the Arrhythmia parameter is 2.076% for ventricular tachycardia Beat Per Minute 160 and 0.494% for Supraventricular Tachycardia Beat Per Minute 200. The design of the Electrocardiograph simulator can simulate the signals of the human body and it can be used as a medium in the learning process in the world of health